Seed characters and their usefulness in the separation of Asteraceae species (Acta Scientiarum. Biological Sciences, 2015)
Studies on seed structure of Asteraceae have received little attention of botanists. Seed structure in Asteraceae is analyzed to evaluate the usefulness of characters in the separation of species through the analysis of nine weedy species. Seeds originate from anatropous, unitegmic and tenuinucellate ovules. The partial collapse of the developing seed coat is a common characteristic in the Asteraceae species studied. The testa consists of crushed and thin-walled cells in almost all of the species studied herein, except for Elephantopus mollis and Parthenium hysterophorus, which showed exotesta cells with U-shaped thickening. The analysis revealed high uniformity in seed characters.